2010
DOI: 10.1042/cbi20090473
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin stimulates clonogenic potential and anti‐inflammatory properties of endothelial progenitor cells

Abstract: EPCs (endothelial progenitor cells) exert vasculoprotective effects and can be used for regenerative therapies. However, several isolation protocols have been described, with inconsistent results. Statins are among the most effective compounds that stimulate EPC numbers in vivo and ex vivo. We aim to describe the effects of rosuvastatin on different subtypes of putative EPCs. EPCs were cultured from mononuclear cells of blood donors and isolated according to three protocols: CFU-EC (colony forming units-endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Relationships between circulating endothelial compartment and IPF characteristics Differences in endothelial cells and progenitors were not associated to the smoking status as it has been shown in other models [37] or with medications with a potential impact on these cells [38] (data not shown). In contrast, they were markedly associated with the Diffusing capacity of the lung for carbon monoxide (DL CO ).…”
Section: Resultsmentioning
confidence: 66%
“…Relationships between circulating endothelial compartment and IPF characteristics Differences in endothelial cells and progenitors were not associated to the smoking status as it has been shown in other models [37] or with medications with a potential impact on these cells [38] (data not shown). In contrast, they were markedly associated with the Diffusing capacity of the lung for carbon monoxide (DL CO ).…”
Section: Resultsmentioning
confidence: 66%
“…Hypercholesterolemic patients, free of diabetes, have been found to have a reduced number of circulating EPCs with impaired function (39,40). A dose-dependent decrease in EPC survival and function was observed with exposure to oxidized LDL, and numerous in vitro and in vivo studies demonstrated that hydroxymethylglutaryl-CoA reductase inhibitors (statins) potently enhance EPC numbers and function (4143). Hypercholesterolemia has also been linked to monocytosis in atherosclerosis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Statins were reported to increase the number of EPC and to promote their functional activity in vivo and ex vivo [88][89][90]. Even if several EPC isolation protocols have been described for the isolation of monocytic or endothelial cell precursors, rosuvastatin showed stimulatory effects on EPCs, independently of the culture protocol [91]. Moreover, statins were reported to directly induce the differentiation of monocytes or CD34-positive hematopoietic precursor cells into EPCs and cardiomyogenic cells [92].…”
Section: Pleiotropic Effects Of Statins In Human Diseases Cardiovascumentioning
confidence: 97%